MENGENAL PENYAKIT BATU GINJAL - Uswatun Hasanah (JURNAL KELUARGA SEHAT SEJAHTERA, 2016)
Kidney stones has been known since the time of ancient Babylonians and Egyptians, a urinary tract stones (urolithiasis) are found in the urinary tract, ranging from kidney calix system, pielum, ureters, bladder and urethra. The cause of the formation of urinary tract stones allegedly associated with urinary tract disorders, metabolic disorders, urinary tract infections, dehydration and other circumstances that remain unclear (idiopathic). Urinary tract stones in general contain elements: calcium oxalate, calcium phosphate, uric acid, magnesium-ammonium-phosphate (MAP), xanthyn and cystine. Understanding the composition of rock found important in the prevention of the possibility of recurrent stone. Presence or absence of a definitive diagnosis of kidney stones can be known through the analysis of urine routine examination (urinalis) and the X-ray examination stomach and abdomen area. Prevention can be done by reducing the types of foods that contain purine like sardines, organ meats, liver, brain, shellfish and other food. Treatment can be done by taking certain drugs for the stones are still small, whereas for large-sized stones that already can be done by way of ESWL (Extra-corporeal Shock Wave Lithotripsy), or by performing surgery.Kata kunci : Urollithiasis, Batu Ginjal, Saluran Kemih, Kalsium Oksalat, KalsiumFosfat, Asam Urat